Une alliance de circonstance : l’Italie et les musulmans d’Albanie (1912-1920) - Renaud Dorlhiac; Fabrice Jesné (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: Ruling an African empire recently formed, Italy sat foot also in Albania at the beginning of the First World War. While its military intervention aimed at securing the Adriatic Sea, it draws Roma to claim protection over the Albanian Muslims in front of the competing powers in the Balkans. The Italian occupation of Albania, that mainly took place in the southern part of the country, also called Northern Epirus, questions the toolbox put in place in order to secure the docility or the support of the populations. The present study tries to emphasize the means and skills mobilized by Italy to cope its rival challenges, and try to carry out its goals in an environment mainly pertaining to the Islamic faith and torn between competing national dynamics. From the review standpoint, we watched carefully to draw a parallel with the rest of the Italian imperial sphere, including the mother country where the issue of keeping law and order had to be addressed acutely.